2009
DOI: 10.1007/s11708-009-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Erosion-corrosion failure of REAC pipes under multiphase flow

Abstract: By using computational fluid dynamics (CFD) modeling and simulation, a predictive method was proposed to explore the erosion failure of reactor effluent air cooler (REAC) pipes with liner under multiphase flow. A theoretical model based on the erosion-corrosion effects of REAC on mixture turbulent flow was proposed for multiphase flow. Effects of various working conditions, liner shapes, and structures, as well as flow parameters on numerical simulations were investigated. Besides, the pipe's erosion-corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For gas-solid two-phase flow, flow erosion has been found the main reason causing the pipeline failures [5][6][7][8][9]. In nitrogen drilling, as the compressed nitrogen is continuously expanding in the rising process along the wellbore, the cuttings-carrying flow rate increases quickly and reaches the peak in the inlet of the discharge pipe.…”
Section: Introductionmentioning
confidence: 99%
“…For gas-solid two-phase flow, flow erosion has been found the main reason causing the pipeline failures [5][6][7][8][9]. In nitrogen drilling, as the compressed nitrogen is continuously expanding in the rising process along the wellbore, the cuttings-carrying flow rate increases quickly and reaches the peak in the inlet of the discharge pipe.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, CFD has become an efficient and robust tool to reveal complex multi-phase flow properties (Sun et al, 2004;Fan et al, 2004;Zhu et al, 2014b). Separate flow erosion studies and flow induced vibration researches by using CFD have been reported (Jin, 1997;Wang and Ni, 2006;Wang, 2009;Zeng et al, 2014;Tang et al, 2009;Ferng and Lin, 2010;Zhang et al, 2007;Oka and Yoshida, 2005), validating the numerical approach. Therefore, in this study, a CFD model coupling with DPM and FSI numerical methods is employed to investigate the flow erosion on a bend in high pressure gas well relief line and flow induced displacement of relief line in the downstream of the bend.…”
Section: Introductionmentioning
confidence: 62%
“…Experimental studies have been carried out by Mazumder et al (2008aMazumder et al ( , 2008b and Deng et al (2005) to identify the location and magnitude of erosion in elbows. Carrying fluid properties, particle content and particle size have been recognized as the significant factors for erosion (Tang et al, 2009;Ferng and Lin, 2010). And several models have been proposed based on experiments for single-phase liquid or gas flow contained solid particles (Zhang et al, 2007;Oka and Yoshida, 2005).…”
Section: Introductionmentioning
confidence: 99%